FINITE ELEMENT STUDY OF VACUUM PRELOADING AND PREFABRICATED VERTICAL DRAINS BEHAVIOR FOR SOFT SOIL IMPROVEMENT - Apriadi, Dedi; Barnessa, Ressa Adrian; Marsa, Nisrina Aulia Is (Jurnal Teknik Sipil, 2019)
AbstractFinite element modeling of soft soil improvement with prefabricated vertical drains (PVD) and vacuum preloading behavior was carried out by considering smear effect and equivalent plane strain based on permeability conversion. Transfer of negative pore pressure due to vacuum preloading was modeled by using pore pressure boundary condition at soft soil layer and along the length of the PVD. The soft soil layer was modeled by using Modified Cam Clay constitutive model. Effect of constant and linearly decreasing vacuum pressure along the PVD length was investigated. Furthermore, prediction from this modeling such settlement was compared to Terzaghi 1-D consolidation. Degree of consolidation for radial only and combined vertical radial were predicted by using Barron?s and Carrillo?s formula, respectively. Numerical evaluation of vacuum preloading-induced lateral deformation compared to conventional preloading was also presented including its comparation with analytical method. Finally, several conclusions and recommendations related to modeling and behavior of combined PVD and vacuum preloading was given.  AbstrakPemodelan elemen hingga perilaku perbaikan tanah lunak dengan vacuum preloading (pembebanan vakum) dan Prefabricated Vertical Drains (PVD) dilakukan dengan mempertimbangkan efek smear dan equivalent plane strain berdasarkan konversi permeabilitas. Transfer negative pore pressure akibat pembebanan vakum dimodelkan dengan menggunakan pore pressure boundary condition pada lapisan tanah lunak dan sepanjang PVD. Lapisan tanah lunak dimodelkan dengan menggunakan model konstitutif tanah Modified Cam Clay (MCC). Pengaruh distribusi tekanan vakum konstan dan bervariasi menurun secara linier di sepanjang PVD akan diteliti. Prediksi penurunan dari pemodelan elemen hingga selanjutnya dibandingkan dengan hasil perhitungan konsolidasi 1-D Terzaghi.  Derajat konsolidasi dihitung menggunakan persamaan Barron untuk arah radial dan Carrillo untuk kombinasi arah vertikal dan radial. Evaluasi numerik perilaku deformasi lateral akibat penggunaan pembebanan vakum dibandingkan dengan preloading (timbunan) juga disajikan berikut perbandingannya terhadap metode analitis. Terakhir, beberapa kesimpulan dan rekomendasi terkait pemodelan dan perilaku kombinasi PVD dan pembebanan vakum diberikan.